The Influence of Social Media Marketing on Customer Decisions-Making Process in Selecting Guesthouses in Maldives - Ali, Hawwa Malsa (ADA University, 2020)
The emergence of the social media has replaced the traditional approach to marketing. Unlike traditional marketing, social media marketing offers a multiple way of communication. With this change, it has impacted almost all the sectors recently. Among this, accommodation sector has changed dynamically due to the influence of social media marketing on customer decision making. Hence, the minor research questions of this study were- how the contents shared by the guesthouses and how the level of customer engagements and interaction of the guesthouses impact customer decision making process in Maldives. Data collected for the research were based on qualitative method. Semi-Structured, telephone interview was used as the data collection technique. The researcher conducted 17 interviews. The findings have revealed that high quality visual contents from guesthouses’ Instagram pages impact the customers decision making process. While participants want to see reviews from Facebook pages. Reviews and word-of mouth has and thus have a significant impact. Further, it showed the customer engagements and communication are vital in selecting a guesthouse. However, customer engagements and communication need be improved from guesthouses through Facebook and Instagram.
Keywords: Business; Social Media Marketing.; Customer Decisions-Making.; Guesthouse -- Maldives.